PENGARUH PEMBERIAN VIDEO EDUKASI DETEKSI DINI KANKER SERVIKS TERHADAP MOTIVASI WANITA USIA SUBUR UNTUK MELAKUKAN PEMERIKSAAN IVA - Anes Patria Kumala; Nui Pawestri; Mera Marhamah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The low achievement of the target of acetic acid visual inspection (IVA) shows that women of childbearing age (WUS) still receive little education about cervical cancer. The use of pocket book media has not shown the results of achieving the IVA examination target. The purpose of this study was to determine the effect of educational videos on early detection of cervical cancer on WUS's motivation to conduct IVA examinations in the Susukan area, East Jakarta. The research method used is quasi-experimental, carried out from May to June 2023 in the Susukan area of East Jakarta. The size of the research sample was 30 subjects obtained from the Lameshow formula. Interest scores before and after the provision of cervical cancer animation education were measured using a questionnaire of 20 questions. Data analysis using paired T test. The results showed that providing educational videos for early detection of cervical cancer increased WUS motivation in IVA examination (p = 0.007). Increased motivation score by 6.37. Cervical cancer education using animated videos can be used by midwives in increasing WUS interest in IVA examination. Educational videos on early detection of cervical cancer are more efficiently accepted by the public than pocket books.